Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let's solve the given equation step-by-step:
The given function is:
[tex]\[ f(x) = \frac{6}{x} - \frac{6}{2x} \][/tex]
We need to set this function equal to 5:
[tex]\[ \frac{6}{x} - \frac{6}{2x} = 5 \][/tex]
First, let's combine the fractions on the left-hand side by finding a common denominator. The common denominator for [tex]\(x\)[/tex] and [tex]\(2x\)[/tex] is [tex]\(2x\)[/tex]:
[tex]\[ \frac{6}{x} - \frac{6}{2x} = \frac{12}{2x} - \frac{6}{2x} \][/tex]
Now, we can combine the terms:
[tex]\[ \frac{12 - 6}{2x} = \frac{6}{2x} = \frac{3}{x} \][/tex]
So the equation simplifies to:
[tex]\[ \frac{3}{x} = 5 \][/tex]
To solve for [tex]\(x\)[/tex], we clear the fraction by multiplying both sides of the equation by [tex]\(x\)[/tex]:
[tex]\[ 3 = 5x \][/tex]
Next, we isolate [tex]\(x\)[/tex] by dividing both sides by 5:
[tex]\[ x = \frac{3}{5} \][/tex]
Hence, the solution for [tex]\(x\)[/tex] is:
[tex]\[ x = 0.6 \][/tex]
So, the value of [tex]\(x\)[/tex] that satisfies the equation [tex]\(\frac{6}{x} - \frac{6}{2x} = 5\)[/tex] is [tex]\(0.6\)[/tex].
The given function is:
[tex]\[ f(x) = \frac{6}{x} - \frac{6}{2x} \][/tex]
We need to set this function equal to 5:
[tex]\[ \frac{6}{x} - \frac{6}{2x} = 5 \][/tex]
First, let's combine the fractions on the left-hand side by finding a common denominator. The common denominator for [tex]\(x\)[/tex] and [tex]\(2x\)[/tex] is [tex]\(2x\)[/tex]:
[tex]\[ \frac{6}{x} - \frac{6}{2x} = \frac{12}{2x} - \frac{6}{2x} \][/tex]
Now, we can combine the terms:
[tex]\[ \frac{12 - 6}{2x} = \frac{6}{2x} = \frac{3}{x} \][/tex]
So the equation simplifies to:
[tex]\[ \frac{3}{x} = 5 \][/tex]
To solve for [tex]\(x\)[/tex], we clear the fraction by multiplying both sides of the equation by [tex]\(x\)[/tex]:
[tex]\[ 3 = 5x \][/tex]
Next, we isolate [tex]\(x\)[/tex] by dividing both sides by 5:
[tex]\[ x = \frac{3}{5} \][/tex]
Hence, the solution for [tex]\(x\)[/tex] is:
[tex]\[ x = 0.6 \][/tex]
So, the value of [tex]\(x\)[/tex] that satisfies the equation [tex]\(\frac{6}{x} - \frac{6}{2x} = 5\)[/tex] is [tex]\(0.6\)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.